2014
DOI: 10.1007/s12031-014-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Cocaine on Tunneling Nanotube Formation and Extracellular Vesicle Release in Glioblastoma Cell Cultures

Abstract: The effects of cocaine (150 nM, 300 nM, and 150 μM) on human glioblastoma cell cultures were studied on tunneling nanotube formation (1-h cocaine treatment) and extracellular vesicle release (1-, 3-, and 8-h cocaine treatment). Cocaine significantly increased the number of tunneling nanotubes only at the lowest concentration used. The release of extracellular vesicles (mainly exosomes) into the medium was stimulated by cocaine at each concentration used with a maximum effect at the highest concentration tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Therefore, it is probable that illicit drug use alters the composition of exosomes during biogenesis due to its cellular affects. The impact of drug use on the exosomal pathway is further exemplified by the observation that cocaine enhanced the release of extracellular vesicles in cell cultures20. Indeed, the effect of illicit drugs goes beyond enhancement of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is probable that illicit drug use alters the composition of exosomes during biogenesis due to its cellular affects. The impact of drug use on the exosomal pathway is further exemplified by the observation that cocaine enhanced the release of extracellular vesicles in cell cultures20. Indeed, the effect of illicit drugs goes beyond enhancement of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 66 ] Human glioblastoma cells also connect via TNTs. [ 67 ] Prion proteins are found to be transported by TNTs in CAD (Cath.‐a‐differentiated) cells, a central nervous system‐derived catecholaminergic neuronal cell line. [ 68,69 ] Studies revealed the presence of TNTs in microvascular endothelial cells and transporting lysosomes and mitochondria.…”
Section: Signaling and Transport Roles Of Tnts And Tnt‐like Protrusiomentioning
confidence: 99%
“…The tumor transition is typified by a shift from a less aggressive, proneural subtype of GBM to a more aggressive mesenchymal subtype (102), which may be mediated in part by GSC EVs (89). Changes in the tumor microenvironment are undoubtedly achieved through combinatorial "armaments," as recipient cells are bombarded not only with EVs containing many proteins, lipids, and RNA species, but also with the secretome of the tumor and potentially with tunneling nanotubes opening direct communication between cells (103). Communication between GBM EVs and the body.…”
Section: Evs In Physiology and Pathology Of The Nervous Systemmentioning
confidence: 99%